The activities of antioxidant enzymes extracted from Fasciola gigantica infecting Thin Tailed and Merino sheep - Wiedosari, Ening (Indonesian Journal of Animal and Veterinary Sciences, 2006)
Previous studies shown that Indonesian Thin Tailed (ITT) sheep are more resistant to Fasciola gigantica infection than Merino sheep. This difference could be mediated by intrinsic defense enzymes of the parasite. Certain enzymes are known to be crucial in parasite survival against host-derived immune responses. We measured some of them to identify if any comparative differences between the enzyme activities of the parasites from the two hosts (ITT & Merino sheep) could account for the mechanisms of parasite resistance to killing by the Merino host and susceptibility to killing by the ITT host. Parasites were extracted from the liver of infected ITT and Merino sheep and superoxide dismutase (SOD), glutathione S-transferase (GST) and catalase (CAT) enzyme activities were assayed. SOD and GST levels were found to be higher in parasites isolated from Merino than those of ITT sheep (P<0.05), CAT activity was not detected in any of the parasites. There was significantly higher eosinophils (P<0,05) in the ITT sheep peritoneal cells. These results suggested that SOD dan GST are important molecules in determining susceptibility in Fasciola-infected Merino sheep and resistance in Fasciola-infected ITT sheep. Key Words: Fasciola Gigantica, Indonesian Thin Tailed Sheep, Merino Sheep, Superoxide Dismutase (SOD), Glutathione S-Transferase (GST)